-4(5+3x)=-30-10x+3

Simple and best practice solution for -4(5+3x)=-30-10x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(5+3x)=-30-10x+3 equation:



-4(5+3x)=-30-10x+3
We move all terms to the left:
-4(5+3x)-(-30-10x+3)=0
We add all the numbers together, and all the variables
-4(3x+5)-(-10x-27)=0
We multiply parentheses
-12x-(-10x-27)-20=0
We get rid of parentheses
-12x+10x+27-20=0
We add all the numbers together, and all the variables
-2x+7=0
We move all terms containing x to the left, all other terms to the right
-2x=-7
x=-7/-2
x=3+1/2

See similar equations:

| -(x-26)=x-4(1-2x | | -4-9m=-49 | | 7=s+$1.75 | | 3x+5=20-0.5 | | 4.2r=25.2 | | 97-3xx=20 | | x(4-x^2)=(-x^2+4) | | 4n−12=12−4n | | 50+100nn=3* | | 2=7(5+a) | | 2z=z-13 | | 3m+4m=16 | | 10=-2t^2+48t+60 | | 4n-7=3 | | 3(2x+6)=15x-3 | | 1.4+8.6+0.7x=-0.05x | | 21=y/3+11 | | 100=5b+10+b-20 | | 3.x+5=17x | | 0=-2t^2+48t+60 | | -3x+15+12x=78 | | 8/5v-1/5v=-49/30 | | 3(2x+6)=15-3 | | 4-7x=2(x-7$ | | g/5+12=23 | | −3(4x+3)+4(6x+1)=4 | | (1÷3)×(y+7)=3×(y-1) | | –8g+3=–9g | | (4x+6)=44° | | 4g+2+8g=56 | | x2x+10=4x+2 | | 2x+4=3x–8 |

Equations solver categories